Correction: Clusters and associations of adverse neonatal events with adult risk of multimorbidity: A secondary analysis of birth cohort data. - Jeeva John; Seb Stannard; Simon D S Fraser; Ann Berrington; Nisreen A Alwan (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0319200.].